(untitled) (Advancements in Homeopathic Research, 2022)
Acne vulgaris is a disease of the pilosebaceous unit that causes non inflammatory lesions (open and closed comedones), inflammatory lesions ( papules, pustules, and nodules), and varying degrees of scaring.1 In these cases homoeopathic medicine are always beneficial when given after individualization of the patient in order to achieve cure. A 22 year old female patient attended outpatient department (OPD) chiefly for the complaints of red pustular and painful eruptions over face. She was under treatment with modern medicine for past sometime but getting no relief so patient turned to homoeopathic treatment. After detailed case taking and repertorisation, Natrum muriaticum 30 was prescribed, within 3 months of homoeopathic treatment, patient showed improvement, only scar of the eruptions remained. Eruptions get subside and no new eruptions are observed in subsequent visits.